1981
DOI: 10.1146/annurev.nu.01.070181.002253
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Significance of Fructose and Sugar Alcohols

Abstract: Human metabolism of D-fructose, D-sorbitol, D-mannitol, and xylitol has been documented. In humans, sorbitol and xylitol at a single oral dose of 20 g or less and fructose at 70 g or less most likely can be fully absorbed. These there sugars can maintain, either independently or nearly independently, the integrity or the carbohydrate requirement for the growth of cells and animals. The absorption of D-mannitol is no more than 80% and is more laxative. In general, there is no adverse effect other than osmotic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
1
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 75 publications
0
70
1
5
Order By: Relevance
“…(21) The median age and weight of those in the xylitol groups whose parents reported mild gastrointestinal side effects was not materially different from the entire study cohort (16.1 months vs. 17.1 months and 10.4 kg vs. 10.9 kg, respectively), so these side effects do not appear to be particularly age-or weight-dependent. It has been shown that adaptation to xylitol and other sugar alcohols occurs rapidly, such that the laxative effect diminishes within several days of beginning regular use (1,11,12); we saw a suggestion of this phenomenon in the declining rate of gastrointestinal side effects in the xylitol groups from month one compared to months two and three.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…(21) The median age and weight of those in the xylitol groups whose parents reported mild gastrointestinal side effects was not materially different from the entire study cohort (16.1 months vs. 17.1 months and 10.4 kg vs. 10.9 kg, respectively), so these side effects do not appear to be particularly age-or weight-dependent. It has been shown that adaptation to xylitol and other sugar alcohols occurs rapidly, such that the laxative effect diminishes within several days of beginning regular use (1,11,12); we saw a suggestion of this phenomenon in the declining rate of gastrointestinal side effects in the xylitol groups from month one compared to months two and three.…”
Section: Discussionmentioning
confidence: 52%
“…(1)It is used widely as a bulking agent in foods and as a low-calorie sweetener in medications, dental care products, chewing gums, and candies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O xilitol além de ser um adoçante alternativo não cariogênico de grande valor sócio-econômico, tem se destacado na área biomédica sendo utilizado na prevenção e combate de patologias como a dermatite atópica (MASAKO et al, 2005a, b), colite pseudo-membranosa (NAABER et al, 1996), otite média aguda (KONTIOKARI; UHARI; KOSKELA, 1998), osteoporose (TISCHLER et al, 1996), anemia hemolítica (WANG; VAN EYS, 1981) e fibrose cística (ZABNER et al, 2000).…”
Section: Introductionunclassified
“…Mannitol은 인체 내에서 원활하게 대사되기 어려우므로, 식 품, 화장품, 의약품 산업 분야에서 저칼로리 감미료 또는 충치 예방 등의 기능성 소재로 활용 가능하다 (Wang and Eys, 1981). 일반적으로 manntiol은 fructose와 glucose를 1:1로 섞은 후, 고온·고압 조건에서 Raney nickel 촉매에 의해 수소화하여 생산되며, 생성된 전환산물은 30% mannitol과 70% sorbitol의 혼합 형태이므로 다시 온도를 낮추고 결정화함으로써 최종적 으로 manntiol만을 회수하게 된다 (Wisnlak and Simon, 1979).…”
unclassified